Framing potentiality in Vona Groarke's X. Issue 4 (3rd April 2023) - Pietrzak, Wit
ABSTRACT: Vona Groarke has long evoked domestic spaces as a means of self-definition in face of a fluid world. Unlike her earlier work, though, in Four Sides Full and X, she finds in architectural constructions, gardens and visual arts a liminal space in which the persona withdraws from the world of action and actuality into a state of potentiality. Although this state is fraught with painful feelings of loneliness, Groarke, in order to resist the seclusion that threatens to engulf her, strives after a radical openness, employing the frames of poetic form inside of which the persona arises as it always already disappears into the framing whiteness of the page.